On Visual and Kinetic Textuality. - Strehovec, Janez (Afterimage)
Focuses on kinetic and animated Web-based poetry pieces that are often developed in distinct time sequences and are usually programmed in Java script, Shockwave, or Flash. Overview of visual language; Information on the basic component of kinetic textuality; Description of trendy activity and various kinds of plays; Lists of visual artists who has been dealing with movable text in electronic format; Importance of visual effects; Discussion on the loop kind of text.